El informativo audiovisual sobre las diferentes manifestaciones culturales que se desarrollan en la Casa de la Cultura Ecuatoriana Benjamín Carrión Núcleo de Loja - Leiva Granda, Marlon Fabián (2016)
This thesis, entitled: AUDIOVISUAL INFORMATION ON THE VARIOUS CULTURAL EVENTS TAKING PLACE IN THE HOUSE OF CULTURE CORE Benjamin Carrion ECUADOR Loja, is a developed and structured according to the academic regulations of the National University of Loja. The central problem of the research was: How can we develop a cultural audiovisual information on the various cultural events taking place in the House of Culture Benjamin Carrion core of Loja (CCE-Nucleus of Loja)? Research has the overall objective: to clarify a cultural audiovisual information on the various cultural events taking place in the (CCE-Nucleus of Loja). The instruments used were the survey where the results obtained from field study revealed the knowledge level about the role that exercise (CCE-Nucleus of Loja) and the needs of users, is taken as reference the question 2. Do you know the activities taking place in the house of Loja core culture? 66 users corresponding to 57% say they do not know the activities developed in the state, as to the question 7. Did you know there audiovisual educational and entertainment programs focusing on art and culture in the city of Loja think? 86 users corresponding to 74% say that no audiovisual program offering this audiovisual format. Applied instruments were interviews where it was determined the need to develop projects aimed at preserving and disseminating the cultural memory and identity, in addition to establishing the main conclusion that users and artists offer support for a television program which is intended to spread culture.